The Effect of Vermicompost Fertilization with the Addition of Organic Waste on the Growth and Quality of Lettuce (Lactuca sativa) - Ariel Mas Pradana; Muhammad Aksan; Muhammad Faisal Saade; Jusman Tang (Edumaspul: Jurnal Pendidikan, 2025)
This study aims to determine the effect of vermicompost fertilization with the addition of organic waste on the growth and quality of lettuce (Lactuca sativa). The research was conducted using an experimental method with several treatments of vermicompost application combined with different levels of organic waste. The observed parameters included plant height, number of leaves, leaf width, fresh weight, and leaf quality. The results showed that the use of vermicompost with the addition of organic waste significantly improved the growth and quality of lettuce compared to the control treatment. Lettuce plants treated with enriched vermicompost exhibited better growth, higher biomass, and superior leaf quality. These findings indicate that vermicompost combined with organic waste can be an effective and environmentally friendly fertilization strategy to enhance lettuce production.